Kinematic comparison of kicking a stationary and rolling ball - Barnes, S.; Sterzing, T.; Ball, K. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Much biomechanical research has examined stationary ball kicking in soccer. However, most kicks in games are performed on a rolling ball. It is important to evaluate this kick as findings for stationary ball kicking might not transfer. The aim of this study was to compare stationary and rolling ball kicks. Nine skilled soccer players performed three kicks under four pre-kick ball conditions (stationary, rolling 30° relative to kick direction, rolling 90° relative to kick direction, dribbling). Lower body kinematics were captured using VICON Nexus (250 Hz), analysed in Visual 3D and compared via a factorial ANOVA. No significant difference existed for foot speed at ball contact, or leg kinematics between stationary and rolling ball conditions Further, kinematics did no change regardless of the approach angle of the ball indicating kinematics do not change regardless of pre-kick ball conditions. Future stationary-rolling ball comparison work should examine kinetics, support leg mechanics and foot to ball interaction.